2008
DOI: 10.2174/157339908783502398
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the Impairment of Reproductive Function: Possible Role of Mitochondria and Reactive Oxygen Species

Abstract: Diabetes Mellitus (DM), a state of chronic hyperglycemia, is a major cause of serious micro and macrovascular diseases, affecting, therefore, nearly every system in the body. Growing evidence indicates that oxidative stress is increased in diabetes due to overproduction of reactive oxygen species (ROS) and decreased efficiency of antioxidant defences, a process that starts very early and worsens over the course of the disease. During the development of diabetes, oxidation of lipids, proteins and DNA increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(111 citation statements)
references
References 97 publications
2
108
0
1
Order By: Relevance
“…Paasch et al (2011) demonstrated higher expression levels of SPANX C, a isomer form of protein, in the sperm of diabetic and obese individuals [48]. This point may be clarified further by examining related studies that have shown poor semen quality accompanied by reduced sperm motility in diabetic individuals [49,50]. SPANX B might be related to energy production in spermatozoa; however further investigation is needed to clarify the exact function of this protein in sperm tail.…”
Section: Discussionmentioning
confidence: 97%
“…Paasch et al (2011) demonstrated higher expression levels of SPANX C, a isomer form of protein, in the sperm of diabetic and obese individuals [48]. This point may be clarified further by examining related studies that have shown poor semen quality accompanied by reduced sperm motility in diabetic individuals [49,50]. SPANX B might be related to energy production in spermatozoa; however further investigation is needed to clarify the exact function of this protein in sperm tail.…”
Section: Discussionmentioning
confidence: 97%
“…Aside from direct treatment of diabetes, research on G. procumbens has also explored its potential in treating infertility, which is one of the complications of diabetes (Ramalho-Santos et al, 2008). G. procumbens was found to exhibit an effect on sexual and reproductive function as the treatment with G. procumbens significantly increased sperm count, sperm motility, and reduced the percentage of sperm mortality of diabetic rats (Sani et al, 2008).…”
Section: Biological Activitiesmentioning
confidence: 99%
“…[12] Studies have shown that men suffering from diabetes have sperms with greater DNA fragmentation and an increase in advanced glycation end products and their receptors (RAGE) leading to deterioration of sperm quality, sperm functions coupled with changes in testicular metabolite levels and spermatogenic gene expression. [192021] Several studies have shown that antioxidant treatment improves glycemic index, reduces diabetic complications, and protects components from oxidative damage. [2223]…”
Section: Introductionmentioning
confidence: 99%